WHERE TEACHING LAGS BEHIND PRACTICE. - Greer, Howard C. (The Accounting Review, 1928)
Abstract Teachers of accounting faces once more the perennial problem of what to teach and how to teach it, there is perhaps even more than ordinary occasion for considering whether accepted methods are acceptable and recognized modes worthy of recognition. On many points there are good reasons for doubt that presentations are sound and on some for certainty that they are not. In matters of record-keeping method and procedure one may be sure of shortcomings when one finds that one is laboriously teaching in the classroom and laboratory methods which have been almost completely superseded or modernized in every well-organized business concern. The purpose of these remarks is the discussion of some instances in point. To the writer it has always seemed curious that teachers of any subject should need to be adjured to keep their teaching abreast of standard practice in their field. Surely the individual whose time is given almost exclusively to research, to reasoning and to elucidation of principles and practices should lead the way in the development of those principles and practices. In accounting instruction, however, there seem always to be many who conceive it as their function merely to learn what is being done in practice-alas, often, no more than what has been done at some past time-and to interpret, explain and justify it to their students.